The role and place of the High Qualifications Commission of Judges of Ukraine in the justice system of Ukraine (Law and Safety, 2022)
It has been established that during the judicial reform in the justice system of Ukraine, bodies of judicial governance were formed – the High Council of Justice and the High Qualification Commission of Judges of Ukraine. These bodies were designed to ensure: organizational conditions for the selection, qualification assessment, career, disciplinary responsibility of judges and their dismissal from office; transparency of court activities; administration of fair and impartial justice; compliance of judges with professional ethics and integrity. It has been proven that the problems of the formation of these bodies and the impossibility of their exercising their powers are an obstacle to solving the issues of the selection of judges, the formation of an independent and professional judicial corps.A comparative analysis of the powers of the High Qualification Commission of Judges of Ukraine and the High Council of Justice as bodies of judicial governance has been carried out, and the prospects for their further functioning for the urgent solution of personnel problems in the sphere of justice have been determined. A number of scientific and practical proposals for amending the current legislation in the context of determining the legal status of the High Qualification Commission of Judges of Ukraine and eliminating the duplication of powers of these bodies related to the selection of judges have been analyzed. The main provisions of the Strategy for the Development of the Justice System and Constitutional Judiciary for 2021–2023 and other legislation on the outlined issues have been characterized.The need to further ensure the institutional independence and transparency of the High Qualification Commission of Judges of Ukraine has been emphasized. The inexpediency of its subordination to the High Council of Justice as a body to ensure the organization of the formation of an honest and highly professional corps of judges has been substantiated. The conclusion has been made about the importance of the existence of the High Qualification Commission of Judges of Ukraine as an independent, autonomous and constitutional body of judicial governance.
Keywords: judicial governance; judicial governance bodies; High Qualifications Commission of Judges of Ukraine; High Council of Justice; justice system of Ukraine; judiciary.